A Retrospective Survey on the Recent Trends in Brain Tumors and their Detection Methodologies - Kiruthiga, G.; Nithyasri, A.; Saravanakumar, N.M. (2025 3rd International Conference on Intelligent Data Communication Technologies and Internet of Things (IDCIoT), 2025)
The abnormal cell growths in the brain are called tumours, and malignant tumours are referred to as "cancer". Scans using CT, MRI, or Positron Emission Tomography (PET) are commonly used to identify brain tissue that is malignant. This study addresses different types of brain tumours, how they are detected, and how to help people who are afflicted by early cancer identification. MRI and PET scans are used to diagnose brain tumours, and additional techniques such as molecular testing, lumbar puncture, and cerebral angiography are utilised to assess the disease stage. This survey investigation aims to: (i) identify abnormal photographs; (ii) segment tumour regions; and (iii) ascertain the cancer's stage. The proper brain tumour detection methodology will be identified with the aid of this survey investigation.